PENERAPAN PENDEKATAN INTEGRATIF DALAM MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PELAJARAN BAHASA INDONESIA SISWA KELAS IV SD - Juwara, Rosniati (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Buton, 2021)
This study aims to improve the students' reading ability on energy sources using an integrative approach to the fourth grade students of SD Negeri 15 Buton. the type of research used is Classroom Action Research (CAR) by adhering to the research design of Arikunto. The results of the increase are shown by the students being able to achieve the minimum completeness criteria score, while the score that has been set by the school is 65. This can be seen from the results of student learning tests in cycle i after using an integrative approach of 29 students, 22 students completed learning, and 7 students did not complete with an average score of 65.68. experienced an increase in the second cycle, namely from 29 students, 24 students who finished studying, and 5 students did not finish learning, with an average value of 73.96. Based on the results of the study, it was concluded that the use of an integrative approach could improve reading comprehension skills in fourth grade students of SD Negeri 15 Buton.